The simulation, regulation capacity assessment and coping strategy of rainstorm runoff waterlogging in Zhu pai-chong Basin of Nanning, China. (15th April 2023) - Li, Qianyun; Yang, Yunchuan; Liao, Haixiang; Liu, Miaoqing; Liao, Liping; Huang, Shanqi; Sun, Guikai; Mo, Chongxun; Li, Xungui
Abstract: Currently, China is experiencing a phase of rapid urbanization. With the frequent occurrence of extreme rainfall events within the context of climate change, the problem of heavy rainfall and waterlogging in many cities is very prominent. In November 2020, China issued a proposal for the construction of sponge cities across the entire region to significantly enhance the rainfall flood prevention and drainage capacity of cities and effectively improve the resilience of sponge city systems for flooding management. Therefore, this paper selected the Zhu pai-chong watershed in Nanning with frequent waterlogging disasters as an example. Based on underlying surface information, We used a coupled SWMM-LISFOOD model to simulate runoff and waterlogging processes and analyze the spatial and temporal evolution characteristics of the basin under 10 designed rainstorm return periods (0.25a-50a). The results confirm the substantial spatial and temporal variabilities of the runoff coefficient in the study area; impermeability was the main factor contributing to high runoff coefficient values. The spatial distribution characteristics of inundation area was general dispersion and local linear aggregation. Furthermore, this study assessed the effect of the control rate of blue‒green‒gray facilities on the actual storms, and the value ranged from only 48.6% (0.25a)-24.05% (50a). This study quantified the two-dimensional distribution of rainfall storage volume thresholds with or without considering the discharged from the pipe network. Quantitative mapping between the elements of "rainfall-storage volume of blue‒green‒gray facilities-runoff-drainage capacity of the pipe network-waterlogging level" was conducted within the study area as an example. Finally, an overall technical process scheme for rainfall and waterlogging management was proposed. The scheme covered the hydrological‒hydraulic mechanism, storage function of sponge facilities, engineering control response, nonengineering measures and intelligent management of rainfall and waterlogging during sponge city construction, which could provide critical scientific support for effective promotion of the construction of sponge cities in China. Graphical abstract: Image 1 Highlights: The runoff waterlogging under different design rainstorm scenarios was simulated. A quantitative method of the regulation level of the total rainstorm is presented. The impact of pipe network drainage on control level of rainstorm is quantified. A system plan to deal with rainstorm waterlogging of sponge city was summarized.